The Managerial Supervision Competence of Supervisors in Improving the Management of Public Senior High Schools in Jambi Province - Sudarmono; Marwazi; Pirhat Abbas (International Journal of Educational and Life Sciences, 2024)
This study examines the managerial supervision competence of supervisors in enhancing the management of public senior high schools in Jambi Province. It focuses on the role of supervisors in improving school leadership through collaborative practices, communication, and strategic planning. Using a qualitative approach, data were collected through interviews with school supervisors, principals, and teachers from selected schools across the province. The findings indicate that effective supervisory practices positively influence school management, particularly in schools where supervisors demonstrate strong leadership and communication skills. The study recommends further professional development for supervisors to address identified challenges and improve school management practices. This research contributes to understanding the relationship between managerial supervision and school improvement in Jambi Province.